(untitled) (CIPEEX, 2022)
SEVERE EOSINOPHILIC ASTHMA IS A CHRONIC DISEASE CHARACTERIZED BY THE ACCUMULATION OF IMMUNE SYSTEM CELLS CALLED EOSINOPHILS, WHICH CONTAIN GRANULES THAT TRIGGER THE MAIN SYMPTOMS OF THE DISEASE, INCLUDING COUGH, MALAISE, DYSPNEA AND FATIGUE. THEREFORE, THE OBJECTIVE OF THIS WORK IS TO REPORT THE CASE AND EXPERIENCE OF A PATIENT WITH SEVERE EOSINOPHILIC ASTHMA ASSOCIETED WITH CHRONIC SINUSITIS FROM DIAGNOSIS TO THE FIRST YEAR OF DISEASE TREATMENT.